COVID-19: Education policy, autonomy and alternative teacher education in Israel (Perspectives in Education, 2021)
The study evaluates an alternative initial teacher education programme launched nationwide by the Israeli Ministry of Education (MoE) at the height of the COVID-19 crisis. The programme aimed to attract unemployed academics to teaching, thereby providing a response to the teacher shortage. To advance the programme, the MoE relaxed its strict regulations and granted the training institutions further autonomy to develop their own programmes. After three months of intensive online training, students were expected to start teaching and continue studying once a week for another year while on the job during their induction year. Since teachers, unlike other hired employees, continued working from home via distance learning during this period, teaching, previously an unattractive profession, turned into a desirable one and hundreds of potential candidates applied for the programme. The research, conducted in one large teacher education college in central Israel, examined the motivations of 125 student teachers to join the teaching profession, their sense of preparedness for teaching, their satisfaction with the programme and their level of commitment to teaching. Findings showed that the student teachers who participated in our research displayed high levels of intrinsic and extrinsic motivations. They reported a high sense of preparedness for teaching, were satisfied with the programme and indicated their commitment to the teaching profession. The results strengthen the importance of tailor-made teacher education programmes and hence the value of greater autonomy in teacher education policy.